Clinical characteristics of myasthenia gravis (MG) patients developing other autoimmune diseases after thymectomy from one single center cohort. Issue 2 (23rd November 2022) - Tian, Wenxin; He, Jing; Yu, Hanbo; Sun, Yaoguang; Wu, Qingjun; Jiao, Peng; Ma, Chao; Huang, Chuan; Li, Donghang; Tong, Hongfeng
Abstract: Background: Myasthenia gravis (MG) patients are reported to have a high risk of other autoimmune diseases (ADs), and thymectomy may increase the risk further. A cohort of MG patients in which thymectomy was performed were investigated to analyze the prevalence, types and features of the new onset ADs. Methods: Consecutive patients with MG who underwent thymectomy at Beijing Hospital between January 2012 and August 2021 were retrospectively enrolled. Patients with a postoperative follow‐up period shorter than a year or incomplete clinical records were excluded. Clinical and follow‐up data were collected. Statistical analyses were performed using SPSS version 22.0. Results: A total of 445 patients were included in this study. The median follow‐up period was 72 months (range, 12–135 months). A total of 63 (14.2%) MG patients had concurrent ADs. The incidence rate was higher than the background prevalence of population (5%), and also higher than that of a former Chinese MG cohort (11.6%). A total of 47 patients (10.6%) were diagnosed with ADs before thymectomy, and 19 (4.3%) developed a new AD after thymectomy. The most common types of new onset ADs after thymectomy were Hashimoto's thyroiditis and rheumatoid arthritis (RA), which were different from those before thymectomy (hyperthyroidism and Hashimoto's thyroiditis). The incidence rate of new onset RA (1.35%) was higher than the frequency of RA before thymectomy (0.45%), and also higher than the incidence rate in a Chinese MG cohort (0.5%). There was a higher proportion of female patients ( p = 0.026) with postoperative ADs. A younger age at operation may increase the risk of nonthymoma MG patients ( p = 0.040) developing ADs. The postoperative treatment effect of MG was similar between patients with and without new onset ADs ( p > 0.05). Conclusions: We observed a higher incidence rate of autoimmune diseases, especially rheumatoid arthritis, in MG patients after thymectomy. The most common types of ADs after thymectomy were different from those before thymectomy. New onset ADs tended to occur in female and young nonthymoma MG patients. The postoperative effect of MG was not related with the new occurrence of ADs. Abstract : A total of 445 myasthenia gravis (MG) patients in which thymectomy was performed were included in this cohort. Nineteen patients (4.3%) developed a new autoimmune disease (AD) after thymectomy. The most common types of new onset ADs after thymectomy were Hashimoto's thyroiditis and rheumatoid arthritis (RA), which were different from those before thymectomy (hyperthyroidism and Hashimoto's thyroiditis). The incidence rate of new onset RA (1.35%, 6/445) was higher than the frequency of RA before thymectomy (0.45%), and also higher than the incidence rate in another Chinese MG cohort (0.5%).